2018
DOI: 10.1177/0269881118795333
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic drug use and pneumonia: Systematic review and meta-analysis

Abstract: Objectives: The purpose of this study was to investigate the association of antipsychotic exposure to the incidence and mortality of pneumonia. Methods: The design of this study involved meta-analysis of observational studies identified from electronic databases. Results: In total, 19 studies were included in the systematic review and 14 in the meta-analysis. Risk of pneumonia was increased by first-generation antipsychotics (risk ratio 1.69, 95% confidence interval 1.34–2.15; five studies), second-generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 54 publications
(113 reference statements)
1
47
3
5
Order By: Relevance
“…The association between psychotropic drugs and pneumonia in older adults varies between drug groups, and some individual drugs, with the majority of research focusing on antipsychotics and BZDs. Systematic reviews and metaanalyses found increased risk of pneumonia associated with antipsychotic [121] and BZD [126] use, but were not specifically focused on the older adult population. Recent studies focusing on the older and potentially more vulnerable population have supported the findings of these systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between psychotropic drugs and pneumonia in older adults varies between drug groups, and some individual drugs, with the majority of research focusing on antipsychotics and BZDs. Systematic reviews and metaanalyses found increased risk of pneumonia associated with antipsychotic [121] and BZD [126] use, but were not specifically focused on the older adult population. Recent studies focusing on the older and potentially more vulnerable population have supported the findings of these systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Herzig et al [122] suggested that there are more than 4000 excess cases of aspiration pneumonia attributable to hospital antipsychotic use each year in the US. The systematic review by Dzahini et al [121] calculated the number needed to harm to be 86 in persons aged 65 years or older based on an incidence of community-acquired pneumonia (CAP) in a study from Spain [162]. Sun et al [126] found a small increase in risk of pneumonia with BZD or BZRD use in their metaanalysis, but the impact on a population level of BZD-or BZRD-associated pneumonia may be substantial given the large number of users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, the Food and Drug Administration (FDA) in the United States, using data from postmarketing surveillance, detected an association between antipsychotic medication exposure and death in patients with dementia, which was partly explained by pneumonia, and required a warning in the package insert about 'esophageal dysmotility and aspiration' for second-generation antipsychotic medications (5,6). In 2008, the FDA further extended the warning to first-generation antipsychotic medications.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, the FDA further extended the warning to first-generation antipsychotic medications. Following this, there have been two attempts to comprehensively review the literature on antipsychotic medication exposure and pneumonia risk (5,7) and an umbrella review of life-threatening medical events after antipsychotic medication exposure, including studies on antipsychotic medication exposure and pneumonia risk (8). These studies suggest that antipsychotic medication exposure is associated with higher rates of pneumonia and that the risk is seen both for firstand second-generation antipsychotic medication.…”
Section: Introductionmentioning
confidence: 99%